2003
DOI: 10.1063/1.1558294
|View full text |Cite
|
Sign up to set email alerts
|

Sheared flow stabilization experiments in the ZaP flow Z pinch

Abstract: The stabilizing effect of a sheared axial flow on the mϭ1 kink instability in Z pinches has been studied numerically with a linearized ideal magnetohydrodynamic model to reveal that a sheared axial flow stabilizes the kink mode when the shear exceeds a threshold. The sheared flow stabilizing effect is investigated with the ZaP ͑Z-Pinch͒ Flow Z-pinch experiment at the University of Washington. An axially flowing Z pinch is generated with a 1 m coaxial accelerator coupled to a pinch assembly chamber. The plasma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 66 publications
(33 citation statements)
references
References 14 publications
1
32
0
Order By: Relevance
“…1,2 Static Z pinches are unstable to the m =0 ͑sausage͒ and m =1 ͑kink͒ modes. 8,9 Z pinches with an embedded flow are generated by coupling a coaxial acceleration region with a pinch assembly region. [3][4][5][6][7] The ZaP Flow Z-Pinch experiment at the University of Washington is presently studying the effect of sheared flow on the stability of the Z pinch.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Static Z pinches are unstable to the m =0 ͑sausage͒ and m =1 ͑kink͒ modes. 8,9 Z pinches with an embedded flow are generated by coupling a coaxial acceleration region with a pinch assembly region. [3][4][5][6][7] The ZaP Flow Z-Pinch experiment at the University of Washington is presently studying the effect of sheared flow on the stability of the Z pinch.…”
Section: Introductionmentioning
confidence: 99%
“…The ZaP experiment (Shumlak et al, 2001(Shumlak et al, , 2003, shown in Fig. 1, produces a hydrogen Z-pinch column (100 cm long and approximately 1 cm radius) with flow velocities on the order of 100-200 km/s (see Table 1 for more information).…”
Section: The Zap Flow Z-pinch Experimentsmentioning
confidence: 99%
“…Measurements and analysis have indicated that ZaP flow Z -pinch plasmas remain stable as a result of sheared axial flows that are generated during the pinch formation process [11], [12], [17], [18]. Instability growth times for static plasmas with similar plasma and magnetic field parameters are on the order of 10 ns.…”
Section: Zap Flow Z -Pinch Experimental Configurationmentioning
confidence: 99%